Intensity-modulated radiation therapy with concurrent chemotherapy followed by durvalumab for stage III non-small cell lung cancer: A multi-center retrospective study. (July 2021) - Tsukita, Yoko; Yamamoto, Takaya; Mayahara, Hiroshi; Hata, Akito; Takeda, Yuichiro; Nakayama, Hidetsugu; Tanaka, Satoshi; Uchida, Junji; Usui, Kazuhiro; Toyoda, Tatsuya; Tamiya, Motohiro; Morimoto, Masahiro; et al.
Highlights: We evaluated the chemoradiotherapy using IMRT for NSCLC in the era of durvalumab. Most patients (81.3%) received durvalumab after chemoradiotherapy using IMRT. The incidence of ≥grade 2 and ≥grade 3 pneumonitis was 35.6% and 8.0%, respectively. V5 ≥58.9% was significantly associated with ≥grade 2 pneumonitis. V5 <60% is recommended to avoid symptomatic pneumonitis in CRT using IMRT. Abstract: Background and purpose: Intensity-modulated radiation therapy (IMRT) is increasingly applied in concurrent chemoradiotherapy (CCRT) for locally-advanced non-small cell lung cancer (NSCLC), with improvement of target coverage and better sparing of normal tissue. IMRT tends to have a larger low-dose irradiation volume than 3D conformal radiotherapy, but the incidence of and risk factors for pneumonitis remain unclear, especially following the approval of durvalumab. Materials and methods: We retrospectively reviewed the records of NSCLC patients treated by CCRT using IMRT at seven Japanese institutions. Primary outcomes were incidence of symptomatic pneumonitis and progression-free survival (PFS). Multivariate logistic regression analysis was used to identify risk factors for ≥grade 2 pneumonitis. Results: Median follow-up from the start of CCRT was 14.3 months ( n = 107 patients; median age 70 years, 29% female). Median lung V5 and V20 was 49.2% and 19.5%, respectively. Durvalumab was administered to 87 patients (81%). Pneumonitis developed in 95 (89%) patients of which 53% had grade 1, 28% grade 2, 6.5% grade 3, and 0.9% grade 4. Durvalumab had been discontinued in 16 patients (18.4%) due to pneumonitis. By multivariate analysis, age ≥70 years, male sex, and V5 ≥58.9% were identified as significantly associated with ≥grade 2 pneumonitis ( p = 0.0065, 0.036 and 0.0013 respectively). The median PFS from the start of CCRT was not reached (95% CI, 14.2 months to not reached) in patients receiving durvalumab. Conclusion: CCRT using IMRT followed by durvalumab was generally effective and tolerable; V5 <60% would be recommended to avoid symptomatic pneumonitis.